Sistem Pakar Mendiagnosa Gangguan Kehamilan Menggunakan Metode Teorema Bayes - Sri Rezeki Marbun; Agustina Simangunsong (Jurnal Sistem Informasi dan Teknologi Jaringan (SISFOTEKJAR), 2021)
Advances in technology are developing very rapidly, and are widely applied in various fields. One of them is in the health sector. As a source of information on various diseases among pregnancy diseases. One of the problems faced by pregnant women during pregnancy is the lack of information about the health of pregnant women. Based on the case study applied to this study, the results show how the process of calculating the probability value of the initial symptoms to the probability of the final symptoms based on the selected symptoms, so it can be concluded that the highest probability of disease is Pre-Eclampsia with a value of 66.6%. And with system that has been built using Visual Basic Studio 2010 and the Ms. Access database, the system can help experts and pregnant women in diagnosing pregnancy disorders.